ANALISIS KINERJA KEUANGAN PADA PT BANK BCA SYARIAH PERIODE 2022-2023 - Norman Alam Hudi; Kukuh Pranggoro; Hisyam Nasir Balfas (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the financial performance of PT Bank BCA Syariah during the 2022-2023 period using profitability ratios, namely Return on Assets (ROA), Return on Equity (ROE), and Operating Expenses to Operating Income (BOPO). The research employs a descriptive quantitative method, utilizing secondary data from the official financial reports of Bank BCA Syariah. The findings reveal that the BOPO ratio increased from 43.20% in 2022 to 62.37% in 2023, maintaining a